2013
DOI: 10.1519/jsc.0b013e31828ddfeb
|View full text |Cite
|
Sign up to set email alerts
|

Performance Enhancement Among Adolescent Players After 10 weeks of Pitching Training With Appropriate Baseball Weights

Abstract: Compared with regulation-weight baseballs, lightweight baseballs generate lower torque on the shoulder and elbow joints without altering the pitching movement and timing. This study investigates the throwing accuracy, throwing velocity, arm swing velocity, and maximum shoulder external rotation (MSER) of adolescent players after 10 weeks of pitching training with appropriate lightweight baseballs. We assigned 24 adolescent players to a lightweight baseball group (group L) and a regulation-weight baseball group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…It has been also recently demonstrated that training induce improvement in the correct tailoring of the APA chain with respect to the prime mover recruitment, both in young adults (Kanekar and Aruin, 2015 ) and elderly (Kubicki et al, 2012 ; Aruin et al, 2015 ). Thus, the increased precision of voluntary movement observed after training (Hamman et al, 1995 ; Yang et al, 2013 ) might be partly due to a more appropriate tuning of APAs on the prime mover recruitment. The linkage between APAs and movement precision was also suggested for intra-limb APAs by Caronni and Cavallari ( 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been also recently demonstrated that training induce improvement in the correct tailoring of the APA chain with respect to the prime mover recruitment, both in young adults (Kanekar and Aruin, 2015 ) and elderly (Kubicki et al, 2012 ; Aruin et al, 2015 ). Thus, the increased precision of voluntary movement observed after training (Hamman et al, 1995 ; Yang et al, 2013 ) might be partly due to a more appropriate tuning of APAs on the prime mover recruitment. The linkage between APAs and movement precision was also suggested for intra-limb APAs by Caronni and Cavallari ( 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…The linkage between APAs and movement precision is also supported by the observation that training induces improvement in the correct tailoring of the APA chain with respect to the prime mover recruitment, both in young adults (Kanekar and Aruin, 2015 ) and elderly (Kubicki et al, 2012 ; Aruin et al, 2015 ). Thus, the increased movement precision observed after training (Hamman et al, 1995 ; Yang et al, 2013 ) might be partly due to a more appropriate tuning of the postural adjustments. Other suggestions about the linkage between APAs and precision derive from some motor behaviors in which proper whole-body stabilization is needed to achieve an effective performance.…”
Section: Apa and Precisionmentioning
confidence: 99%
“…In a baseball game, pitchers play a key role in determining the outcome of the game, while the velocity and accuracy of pitches thrown by the pitchers are considered to be very important factors ( Yang et al, 2013 ). The ability to throw a ball at a high velocity requires a strong upper extremity muscle and a high power to generate maximum muscle strength within a short timeframe during the pitching motion ( Potteiger et al, 1989 ).…”
Section: Introductionmentioning
confidence: 99%